Whole exome sequencing identifies de novo heterozygous CAV1 mutations associated with a novel neonatal onset lipodystrophy syndrome. (21st April 2015) - Garg, Abhimanyu; Kircher, Martin; del Campo, Miguel; Amato, R. Stephen; Agarwal, Anil K.; University of Washington Center for Mendelian Genomics
<x xml:space="preserve">Abstract</x> Despite remarkable progress in identifying causal genes for many types of genetic lipodystrophies in the last decade, the molecular basis of many extremely rare lipodystrophy patients with distinctive phenotypes remains unclear. We conducted whole exome sequencing of the parents and probands from six pedigrees with neonatal onset of generalized loss of subcutaneous fat with additional distinctive phenotypic features and report de novo heterozygous null mutations, c.424C>T (p.Q142*) and c.479_480delTT (p.F160*), in CAV1 in a 7‐year‐old male and a 3‐year‐old female of European origin, respectively. Both the patients had generalized fat loss, thin mottled skin and progeroid features at birth. The male patient had cataracts requiring extraction at age 30 months and the female patient had pulmonary arterial hypertension. Dermal fibroblasts of the female patient revealed negligible CAV1 immunofluorescence staining compared to control but there were no differences in the number and morphology of caveolae upon electron microscopy examination. Based upon the similarities in the clinical features of these two patients, previous reports of CAV1 mutations in patients with lipodystrophies and pulmonary hypertension, and similar features seen in CAV1 null mice, we conclude that these variants are the most likely cause of one subtype of neonatal onset generalized lipodystrophy syndrome. © 2015 Wiley Periodicals, Inc.